Georgia's Planting Prelate - Swanson, Drew A. (Georgia Open History Library, 1945)
Georgia's Planting Prelate consists of notes on the life of the Reverend Stephen Elliott, a bishop of the Protestant Episcopal Church in the mid-1800s and the only presiding bishop of the Protestant Episcopal Church in the Confederate States of America. These notes are accompanied by the full text of the bishop's address on horticulture given in 1851 in Macon, which displays his remarkable knowledge of southern agriculture. The Georgia Open History Library has been made possible in part by a major grant from the National Endowment for the Humanities: Democracy demands wisdom. Any views, findings, conclusions, or recommendations expressed in this collection, do not necessarily represent those of the National Endowment for the Humanities.